STUDY OF BIRD DIVERSITY IN THE SRIWIJAYA KINGDOM'S ANCIENT PARK - Helida, Asvic; Susilawati, Oktavia; Syahroni, S.P, M.Si, Sasua Hustati; Azhar, Khorik (Sylva Jurnal Ilmu-ilmu Kehutanan, 2023)
Birds need habitat conditions that are suitable and safe from all kinds of disturbances, which can be an important factor in the presence of birds in a place. The aim of this research is to analyze the diversity of bird species and the factors that influence the existence of bird species in the Sriwijaya Royal Archaeological Park, Palembang. The method used in this research is quantitative descriptive data taken using the "point count" or IPA (Index Point of Abundance) method, namely by recording the number of bird populations and then processing the data to determine the species richness index, species diversity index and species evenness index. The research results obtained by the richness of bird species in the Sriwijaya Royal Archaeological Park include high criteria. This is shown by the results of calculating the bird richness index which obtained an average value of R index > 5.0, which is included in the high criteria and the species evenness index in each transect is low. , because it is less than <0.3. The diversity of bird species in the Sriwijaya Royal Archaeological Park is relatively low. This is caused by trees that grow less densely, making the availability of food for birds insufficient. Apart from that, the factors that influence this are the distribution of species, dominance, limiting factors, competition, and the presence of predators and a supportive environment so that some species can spread in the area. The factor that influences bird species in the Sriwijaya Royal Archaeological Park, Palembang City, is land cover.